The role of extravillous trophoblasts and uterine NK cells in vascular remodeling during pregnancy - Wei, Xiao-Wei; Zhang, Yu-Chen; Wu, Fan; Tian, Fu-Ju; Lin, Yi (Frontiers in Immunology, 2022)
Successful embryo implantation requires both a receptive endometrium and competent blastocysts. After implantation, the maternal decidua undergoes a series of changes, including uterine spiral artery (SA) remodeling to accommodate the fetus and provide nutrients and oxygen for the fetus to survive. Uterine spiral arteries transform from small-diameter, high-resistance arteries to large-diameter and low-resistance arteries during pregnancy. This transformation includes many changes, such as increased permeability and dilation of vessels, phenotypic switching and migration of vascular smooth muscle cells (VSMCs), transient loss of endothelial cells (ECs), endovascular invasion of extravillous trophoblasts (EVTs), and presence of intramural EVT, which are regulated by uterine NK (uNK) cells and EVTs. In this review, we mainly focus on the separate and combined roles of uNK cells and EVTs in uterine SA remodeling in establishing and maintaining pregnancy. New insight into related mechanisms will help us better understand the pathogenesis of pregnancy complications such as recurrent pregnancy loss (RPL) and preeclampsia (PE).